Policy on Implementing the Results of Facial Recognition Examination to Support the Disclosure of Criminal Acts with Minimal Fingerprint Evidence - Fajrin, Suci; Tri Bawono, Bambang (UNISSULA Semarang, 2025)
Abstract. Modern law enforcement requires technological support capable of strengthening criminal investigations, particularly when conventional evidence such as fingerprint traces is unavailable or insufficient. One of the recurring challenges in criminal investigations is the absence of fingerprint evidence, which has long served as a primary tool for identifying perpetrators. This study aims to analyze the policy implementation of facial recognition examination in supporting the disclosure of criminal acts with minimal fingerprint evidence, using a case study of forgery and land embezzlement reported under Police Report Number LP/B/24/I/2024/SPKT/BARESKRIM POLRI dated January 19, 2024. This research employs a normative-empirical legal method with a qualitative descriptive approach. Primary and secondary legal materials are analyzed using the theory of legal certainty and the legal system theory to evaluate the legality, effectiveness, and challenges surrounding the use of facial recognition technology in criminal justice proceedings. The findings indicate that facial recognition plays a strategic role in directing investigations when fingerprint evidence is absent and successfully revealed the actual identity of the individual impersonating the rightful landowner in this case. However, facial recognition cannot serve as a standalone primary evidence; instead, it functions as supplementary indicative evidence that must be corroborated with other lawful evidence in accordance with the Criminal Procedure Code (KUHAP) and the Electronic Information and Transactions Law. This study concludes that the use of facial recognition in criminal investigations represents a significant advancement in digital evidence, yet it still encounters challenges involving the absence of specific regulations, potential algorithmic bias, and concerns regarding personal data protection. Therefore, clear regulatory frameworks, national forensic standards, and capacity-building for law enforcement officers are essential to ensure that this technology is applied accountably and in accordance with the principle of legal certainty.